2011
DOI: 10.1100/tsw.2011.36
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors, Their Ligands, and Atherosclerosis

Abstract: Atherosclerosis is a disease characterized by inflammation in the arterial wall. Atherogenesis is dependent on the innate immune response involving activation of Toll-like receptors (TLRs) and the expression of inflammatory proteins. TLRs, which recognize various pathogen-associated molecular patterns, are expressed in various cell types within the atherosclerotic plaque. Microbial agents are associated with an increased risk of atherosclerosis and this is, in part, due to activation of TLRs. Recently consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 190 publications
0
29
0
1
Order By: Relevance
“…46 TLR signaling leads to activation of transcription factors, such as nuclear factor-κB, that promote proinflammatory activity, contributing to the development of phenotypically distinct foam cells. 21,43,[47][48][49][50][51] First, TLRs induce foam cell formation by increasing the uptake of lipoproteins and the storage of lipid (via increases in CD36, AP2, fatty acid-binding proteins, MyD88-adaptor-like, adipose differentiation-related protein, lipin 1, glycerol-3-phosphate acyltransferase 3, and diacylglycerol O-acyltransferase 2). 52,53 Second, TLRs decrease the delivery of cholesterol macrophages to high-density lipoprotein (HDL), the first step in reverse cholesterol transport (via decreases in macrophages ATP-binding cassette transporter subfamily A (ABCA)-1, ATP-binding cassette transporter subfamily G, scavenger receptor class B, member 1/CD36 antigen-like 1, and apolipoprotein E).…”
Section: Monocyte Migration and Differentiation Of Macrophage And Foamentioning
confidence: 99%
“…46 TLR signaling leads to activation of transcription factors, such as nuclear factor-κB, that promote proinflammatory activity, contributing to the development of phenotypically distinct foam cells. 21,43,[47][48][49][50][51] First, TLRs induce foam cell formation by increasing the uptake of lipoproteins and the storage of lipid (via increases in CD36, AP2, fatty acid-binding proteins, MyD88-adaptor-like, adipose differentiation-related protein, lipin 1, glycerol-3-phosphate acyltransferase 3, and diacylglycerol O-acyltransferase 2). 52,53 Second, TLRs decrease the delivery of cholesterol macrophages to high-density lipoprotein (HDL), the first step in reverse cholesterol transport (via decreases in macrophages ATP-binding cassette transporter subfamily A (ABCA)-1, ATP-binding cassette transporter subfamily G, scavenger receptor class B, member 1/CD36 antigen-like 1, and apolipoprotein E).…”
Section: Monocyte Migration and Differentiation Of Macrophage And Foamentioning
confidence: 99%
“…HSP70 can interact with the VSMCs, the major producer of ECM proteins, through the TLR4. The authors demonstrated that extracellular HSP70 binds to human aorta smooth muscle cell TLR4, which upregulated the [273] ; with own modification).…”
Section: Atherosclerosismentioning
confidence: 93%
“…TLR activation of the endothelium promoted lipid and leukocyte accumulation within lesions [75] . TLRs ligands are expressed in various cell types within the atherosclerotic plaque [273] . TLR1, TLR2, and TLR4 were upregulated in human atheroma with active NF-κB colocalizing with TLR2 and TLR4 in the plaque [263] .…”
Section: Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [6] further found an increased collagen and elastin plaque content indicating a more stable plaque, while macrophage infiltration, the expression of cathepsin S protein (CatS) and toll-like receptor (TLR) 2 were reduced. TLR play an important role in the innate immune system and several lines of evidence indicate an association with atherosclerosis [8]. CatS is an excreted lysosomal protease which is linked to extracellular matrix degradation such as elastin and collagen and therefor potentially responsible for plaque destabilization [9].…”
mentioning
confidence: 99%